PROSPEK PENINGKATAN KUALITAS KOMPONEN PARIWISATA DI KERATON SURAKARTA - Rusdiana Putri, Devi; Marsoyo, Agam (Jurnal IPTA (Industri Perjalanan Wisata); Vol 7 No 1 (2019): Jurnal IPTA (July 2019)DO - 10.24843/IPTA.2019.v07.i01.p08, 2019)
Surakarta and Yogyakarta Palace are two palaces that historically connected and both are located in the middle of Surakarta dan Yogyakarta region. They offer nearly the same tourist products, but they have significantly different tourist numbers. Whereas, Surakarta Palace itself has various potential tourist attractions to visit. This study aimed to measure quality and define the prospect of tourism component development in Surakarta Palace. This research used questionnaire with random sampling technique which later supported by observation and interview to the parties concerned. This study found out that : (1) the tourism component quality in Surakarta palace is different compared to Yogyakarta palace due the lack of diversity in attractions and limited amenities choices. (2) But Surakarta Palace has wide range of potential that can be well-developed. (3) The support from local government and community have not enough yet to encourage the improvement of tourism component’s quality in Surakarta Palace.